Analisis Penerapan Pembiayaan Murabahah Berdasarkan PSAK No. 102 di Bank Syari’ah Indonesia KCP Situbondo Basuki Rahmat - Indah Eka Putri; Imamatin Listya Putri; Imro'atun Shoimah (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
Murabahah is selling an item at a selling price of the acquisition plus an agreed margin or profit and the seller must disclose the acquisition price of the item to the buyer. With the principle of buying and selling goods at the original price with additional agreed profits, with the bank as the seller and the costumer as the buyer. In murabahah, the goods being traded must be available at the time of the contract, while payments can be made in cash or in installments. So the researchers focused on research on how to apply murabahah financing and how to apply murabahah financing at BSI KCP Situbondo Basuki Rahmat based on PSAK No. 102. To describe the application of murabahah financing at BSI KCP Situbondo Basuki Rahmat based on PSAK No. 102. The research method that the researcher used was a qualitative research method. The results of this research indicate that the implementation of murabahah financing carried out at BSI KCP Situbondo Basuki Rahmat has not fully implemented PSAK No. 102 because the murabahah contract implemented at BSI KCP Situbondo Basuki Rahmat only applies murabahah financing with orders and does not apply murabahah financing without orders. The recognition, measurement, presentation and disclosure made at BSI KCP Situbondo Basuki Rahmat has been applied in accordance with PSAK No. 102.